Students’ Challenges with Task Repetition in Grammar Classes - Alawiyah, Nur -; Zur, Sarjaniah; Musthan, Zulkifli (IAIN KENDARI, 2025)
This study aims to investigate students' challenges in learning grammar using the task repetition approach in collaborative writing and video-based tasks. Using a qualitative approach, data were collected through semi-structured interviews with second semester students at an Islamic higher education institution in Southeast Sulawesi and then analysed using thematic analysis. The findings revealed that most participants had both positive and negative experiences. However, this study emphasises the number of challenges that students face when repeating assignments. The main challenges are categorized into two main areas: task performance and collaboration. The findings underline the importance of understanding and addressing these negative experiences in order to design effective interventions to support students in online collaborative learning environments. It also provides valuable insights for educators aiming to improve teaching strategies and students' collaborative task performance. Keywords: Task repetition; students’ challenges, learning Grammar